Pengaruh Struktur Aktiva, Total Asset Turn Over, Current Ratio dan Debt to Equity Ratio terhadap Return On Asset pada Perusahaan Sub Sektor Farmasi - Muhammad Rizki Bima Putra; Alwi Alwi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The aim of this research is to determine the effect of asset structure, total asset turnover, current ratio and debt to equity ratio on return on assets in pharmaceutical sub-sector companies. Pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period are the population for this research, selected using a purposive sampling technique. The data analysis used is classical assumption testing, multiple linear regression analysis, correlation coefficient analysis and determination coefficient analysis, partial testing and simultaneous testing. This research uses SPSS 25 with 27 data samples. This research shows that asset structure, current ratio and debt to equity ratio have a significant influence on return on assets. On the other hand, total asset turnover does not have a significant influence on return on assets.